Inter-relationships between machine squat-jump strength, force, power and 10 m sprint times in trained sportsmen - Harris, N. K.; Cronin, J. B.; Hopkins, W. G.; Hansen, K. T. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: Strength and conditioning practitioners appear focussed on developing maximal strength based on the premise that it underpins explosive muscular performance. Investigation into the relationship between strength and a multitude of explosive power measures is limited though. Furthermore, the relationship of explosive force and power with functional performance is unclear. METHODS: We examined the inter-relationships between maximal strength and explosive measures of force and power at different loads. Also investigated were the relationships between explosive measures and 10-m sprinting ability. Forty elite-level well-trained rugby union and league athletes performed 10-m sprints followed by bilateral concentric-only machine squat-jumps at 20 and 80%1RM. The magnitudes of the inter-relationships between groups of force measures, power measures and sprint times were interpreted using Pearson correlation coefficients, which had uncertainty (90% confidence limits) of ~±0.25. Measures investigated included peak force, peak power, rate of force development, and some of Zatsiorsky`s explosive measures, all expressed relative to body mass. RESULTS: The relationship between maximal strength and peak power was moderate at 20 %1RM (r=0.32) but trivial at 80 %1RM (r=-0.03). Practically no relationship between any of the explosive measures and 10-m sprint ability was observed (r=-0.01 to 0.06). CONCLUSION: Although correlations do not imply cause and effect, we speculate that the common practice of focussing on high levels of maximal strength in a machine squat to improve power output may be misguided. Our results also cast doubt on the efficacy of increasing explosive force and power in a machine squat-jump with the intention of improving sprint ability in well-trained athletes.